Medicinal Mushroom Growth as Affected by Non-Axenic Casing Soil - Zied, D. C. [UNESP]; Minhoni, M. T. A. [UNESP]; Kopytowski-Filho, J. [UNESP]; Barbosa, L. [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP] (Science China Press, 2011)
Ten different casing soils were collected from two soils at two depths (0.2 and 2.0 m below soil surface) to examine the relationships between the physical properties of non-axenic casing soil and yield, number and weight of the medicinal mushroom Agaricus blazei ss. Heinemann. The results showed that soil clay content and bulk density were negatively correlated with the mushroom yield, respectively, but soil silt content and water-holding capacity were found to be positively correlated with the yield. The number of mushrooms was negatively correlated with soil water-holding capacity but positively correlated with soil clay, bulk density and porosity. The weight of mushroom was positively correlated with the content of soil fine sand and negatively correlated with the contents of soil coarse sand, total sand and clay. Neither soil depth nor different soil combinations affected the yield and number of mushrooms, but the mushroom weight was affected by the soil combinations and soil depth, so interplay in the fructification process with the physical characteristics of casing is complicated.
Keywords: Agaricus blazei; casing layer; quality factors; soil depth; soil particles